Climate Projection of Dongjiang River Basin Based on Statistical Downscaling Methods - DU Yi (Renmin Zhujiang)
For higher reliability of climate projections in the Dongjiang River Basin,various methods are used to statistically downscale the air temperature and precipitation output generated by the global climate model CanESM2.The results reveal that SDSM and Delta have good downscaling simulations on the temperature and precipitation in the Dongjiang River Basin,respectively.For temperature,the daily minimum temperature will increase by 2.26 ℃ (RCP4.5) and 3.65 ℃ (RCP8.5);the daily mean temperature will increase by 2.70 ℃ (RCP4.5) and 4.69 ℃ (RCP8.5),and the daily maximum temperature will increase by 2.79 ℃ (RCP4.5) and 4.95 ℃ (RCP8.5) by the end of the 21st century (2081—2100) relative to the benchmark period (1961—2005).In terms of precipitation,the annual precipitation will rise at a rate of 16.4 mm/10a,8.7 mm/10a,and 25.4 mm/10a under the RCP2.6,RCP4.5,and RCP8.5 scenarios,respectively.In addition,the temperature increase is more prominent in summer and winter,while precipitation increases more in summer and autumn.Overall,the risk of temperature extremes and precipitation extremes in the Dongjiang River Basin during the flood season may increase in the future.